2008
DOI: 10.1002/jmri.21343
|View full text |Cite
|
Sign up to set email alerts
|

Interstudy reproducibility of SSFP cine magnetic resonance: Impact of magnetic field strength and parallel imaging

Abstract: Purpose:To study the effects of field strength and parallel imaging on image contrast and interstudy reproducibility of right and left ventricular (RV and LV) measurements using steady-state free precession (SSFP) cardiovascular magnetic resonance (CMR). Materials and Methods:Thirty-two subjects (20 normal, 12 cardiac patients) underwent four SSFP cine short-axis imaging studies: two at 1.5T, one at 3T, and another at 3T with parallel imaging (SENSE). RV and LV contrast-to-noise ratios (CNRs) were compared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
2
11
0
1
Order By: Relevance
“…Comparative analyses of LV function indexes, mass, and volume using cine SSFP has shown no significant difference in values obtained at 3.0T compared to 1.5T [47,48]. Therefore, one can use existing knowledge and experience of MR quantification algorithms for 3.0T imaging.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative analyses of LV function indexes, mass, and volume using cine SSFP has shown no significant difference in values obtained at 3.0T compared to 1.5T [47,48]. Therefore, one can use existing knowledge and experience of MR quantification algorithms for 3.0T imaging.…”
Section: Resultsmentioning
confidence: 99%
“…LV mass, LV end‐diastolic volume, LV wall thickness, and LVEF reported here were calculated from short‐axis sequences, where papillary muscles were included in LV mass and excluded from LV volume 26. There was no difference in interstudy reproducibility (test/retest) between the baseline and follow‐up studies done at different field strengths 27. Concentricity was defined as LV mass (g) divided by LV volume (mL).…”
Section: Methodsmentioning
confidence: 99%
“…The unavoidable variations in diaphragm position with each breathhold can lead to slice-dependent shifting of the cardiac anatomy within the imaging volume [3], which has been shown to contribute to inter-examination variability in LV functional parameters [4]. As shown on a more recent 1.5 T MR scanner, reproducibility in patient populations has improved [5], where test-retest studies of ejection fraction and mass have been shown to be more variable for patients with congestive heart failure with respect to other conditions and healthy controls [6]. Furthermore, performing multiple breathholds in quick succession can lead to fatigue [7], especially in patients with poor cardiac and respiratory function, where hyperventilation with room air allowed an average breathhold duration of just 12 s [8].…”
Section: Introductionmentioning
confidence: 99%